2019
DOI: 10.1111/cid.12751
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of clinical and radiographic periimplant status around narrow and regular diameter implants placed in cigarette‐smokers and nonsmokers

Abstract: Background To date, no clinical investigation has assessed the clinical and radiographic indices around narrow diameter implants (NDIs) and regular diameter implants (RDIs) in individuals with cigarette smoking habit and nonsmokers. Objective To estimate and compare the clinical and radiographic indices around NDIs (< 3.3 mm) and RDIs placed in cigarette smokers (CS) and nonsmokers (NS). Materials and Methods Eighty‐six patients requiring implant surgery in the anterior mandible were divided into two groups (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
1
10
0
1
Order By: Relevance
“…[13][14][15][16] Besides poor oral hygiene, habitual tobacco-smoking in the form of cigarettes and waterpipe-tobacco are well-renowned risk factor of peri-implant diseases. 13,[17][18][19][20][21][22] According to ArRejaie et al 18 levels of destructive inflammatory cytokines (matrix-metallo-proteinase-9 and IL-1beta) are significantly higher in the peri-implant sulcular fluid (PISF) of cigarette-smokers compared with never-smokers (patients that never used tobacco in any form). These cytokines have been reported to contribute towards worsening the peri-implant soft tissue plaque index (PI), gingival index (GI), and probing depth; and increasing crestal bone loss (CBL) on the mesial and distal surfaces of the implant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16] Besides poor oral hygiene, habitual tobacco-smoking in the form of cigarettes and waterpipe-tobacco are well-renowned risk factor of peri-implant diseases. 13,[17][18][19][20][21][22] According to ArRejaie et al 18 levels of destructive inflammatory cytokines (matrix-metallo-proteinase-9 and IL-1beta) are significantly higher in the peri-implant sulcular fluid (PISF) of cigarette-smokers compared with never-smokers (patients that never used tobacco in any form). These cytokines have been reported to contribute towards worsening the peri-implant soft tissue plaque index (PI), gingival index (GI), and probing depth; and increasing crestal bone loss (CBL) on the mesial and distal surfaces of the implant.…”
Section: Introductionmentioning
confidence: 99%
“…A dilemma in clinical implant dentistry and related research is the prevention and treatment of dental implant‐related diseases 13‐16 . Besides poor oral hygiene, habitual tobacco‐smoking in the form of cigarettes and waterpipe‐tobacco are well‐renowned risk factor of peri‐implant diseases 13,17‐22 . According to ArRejaie et al 18 levels of destructive inflammatory cytokines (matrix‐metallo‐proteinase‐9 and IL‐1beta) are significantly higher in the peri‐implant sulcular fluid (PISF) of cigarette‐smokers compared with never‐smokers (patients that never used tobacco in any form).…”
Section: Introductionmentioning
confidence: 99%
“…6 Other variables that may affect PS encompass implant dimensions (length and diameter), surface characteristics (moderately rough or smooth), and number of threads on the implant surface. 3,[7][8][9][10][11] With regard to implant diameter, studies [12][13][14][15] have shown that narrow-(<3.3 mm) and standard-(4.1 mm) diameter dental implants can remain functionally stable in smokers and medically compromised patient in a manner similar to systemically healthy nonsmokers. However, achievement of PS is often challenging when implants are placed in type-IV bone (soft bone), which usually comprises the posterior maxillae.…”
Section: Introductionmentioning
confidence: 99%
“… 6 An agreement regarding the absolute diameter of NDIs is yet to be reached; however, in indexed literature, dental implant with a diameter of up to 3.5 mm are considered NDIs. 7 , 8 According to Ma M et al 9 NDIs can successfully support single-tooth supported implants in the posterior maxillae in a way similar to regular or SDIs. Moreover, 3-year prosthesis success rates for NDIs and SDIs have been reported as 89.25% and 96.55%, respectively.…”
Section: Introductionmentioning
confidence: 99%